Pengaruh Kepemimpinan Kepala Sekolah dan Kinerja Guru Terhadap Kualifikasi Mutu Internal Gugus Sekolah Dasar Negeri Lampanah Aceh Besar - Iswani, Iswani; Akmaluddin, Akmaluddin; Novita, Rita (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This study aims to analyze the influence of the principal's leadership and teacher performance on the internal quality qualifications of the Lampanah Aceh Besar State Elementary School cluster. This study uses a quantitative approach with a type of causality research because it wants to see cause and effect or influence between variables, namely the influence of principal leadership and teacher performance on the internal quality qualifications of the Lampanah Aceh Besar State Elementary School Cluster. The research sample amounted to 41 respondents who were selected using a simple random sampling technique. Data was collected using a closed questionnaire. Data analysis using multiple linear regression test and t test. Based on the results of the study, the leadership of the principal and teacher performance simultaneously have a significant impact on internal quality qualifications in the Lampanah Aceh Besar State Elementary School Cluster.